Performance measures for lower gastrointestinal endoscopy: a European Society of Gastrointestinal Endoscopy (ESGE) quality improvement initiative. Issue 3 (April 2017) - Kaminski, Michal F; Thomas-Gibson, Siwan; Bugajski, Marek; Bretthauer, Michael; Rees, Colin J; Dekker, Evelien; Hoff, Geir; Jover, Rodrigo; Suchanek, Stepan; Ferlitsch, Monika; Anderson, John; Roesch, Thomas; et al.
The European Society of Gastrointestinal Endoscopy and United European Gastroenterology present a short list of key performance measures for lower gastrointestinal endoscopy. We recommend that endoscopy services across Europe adopt the following seven key performance measures for lower gastrointestinal endoscopy for measurement and evaluation in daily practice at a center and endoscopist level:1 rate of adequate bowel preparation (minimum standard 90%);2 cecal intubation rate (minimum standard 90%);3 adenoma detection rate (minimum standard 25%);4 appropriate polypectomy technique (minimum standard 80%);5 complication rate (minimum standard not set);6 patient experience (minimum standard not set);7 appropriate post-polypectomy surveillance recommendations (minimum standard not set). Other identified performance measures have been listed as less relevant based on an assessment of their importance, scientific acceptability, feasibility, usability, and comparison to competing measures.